Patent Foramen Ovale in Patients with Sickle Cell Disease and Stroke: Case Presentations and Review of the Literature - Sheila Razdan; John J. Strouse; Rakhi Naik; Sophie Lanzkron; Victor Urrutia; Jon R. Resar; Linda M. S. Resar (Case Reports in Hematology)
Although individuals with sickle cell disease (SCD) are at increased risk for stroke, the underlying pathophysiology is incompletely understood. Intracardiac shunting via a patent foramen ovale (PFO) is associated with cryptogenic stroke in individuals without SCD. Recent evidence suggests that PFOs are associated with stroke in children with SCD, although the role of PFOs in adults with stroke and SCD is unknown. Here, we report 2 young adults with SCD, stroke, and PFOs. The first patient had hemoglobin SC and presented with a transient ischemic attack and a subsequent ischemic stroke. There was no evidence of cerebral vascular disease on imaging studies and the PFO was closed. The second patient had hemoglobin SS and two acute ischemic strokes. She had cerebral vascular disease with moyamoya in addition to a peripheral deep venous thrombosis (DVT). Chronic transfusion therapy was recommended, and the DVT was managed with warfarin. The PFO was not closed, and the patients' neurologic symptoms were stabilized. We review the literature on PFOs and stroke in SCD. Our cases and the literature review illustrate the dire need for further research to evaluate PFO as a potential risk factor for stroke in adults with SCD.